The world atlas of public art - Wasserman, Andrew (New Haven ;London Yale University Press, 2024)
"A towering abstract steel sculpture in the middle of a traffic island in Spoleto, Italy. Soaring vertical gardens enhanced with digital technology in Singapore's Marina Bay. A skateboard bowl that doubles as a community pool in San Juan, Puerto Rico. These are just a few of the contemporary public artworks defining cities around the globe that are featured in The World Atlas of Public Art. The book charts a global survey of works and practices from the past six decades featuring more than 125 significant permanent and temporary public artworks by leading contemporary artists, including Ruth Asawa, Christo and Jeanne-Claude, Olafur Eliasson, Yayoi Kusama, Simone Leigh, and OSGEMEOS. Readers encounter works in chapters on six public locations: grounds, walls, structures, waters, routes, and skies. Organized geographically within these chapters, the book reveals not only where to find these artworks but also how they generate meaning from their location. Between the chapters are essays on the themes of public bodies, gatherings, platforms, services, and debates. Enlivened with more than 300 energetic and eye-catching images, this book is an exploration of how art transforms public spaces, promotes social interaction, fosters community, and provokes impassioned responses."
Public grounds -- Public walls -- Public structures -- Public waters -- Public routes -- Public skies.
Includes bibliographical references and index.
Keywords: Public art -- Pictorial works; Art -- Intégration à l'architecture -- Ouvrages illustrés; Illustrated works